A New Perspective: Administrator Recommendations for Reducing Child Welfare Turnover. Issue 5 (19th October 2020) - Griffiths, Austin; Collins-Camargo, Crystal; Horace, Angelique; Gabbard, Jay; Royse, David
ABSTRACT: Child maltreatment impacts society on multiple levels, and consistent turnover in the child welfare workforce creates financial challenges and problems associated with service delivery. This study explores the qualitative survey findings from a statewide sample of child welfare administrators in one state (n = 86). When asked to provide suggestions for improving workforce retention, nine overarching themes emerged: compensation, decreased workload, organizational culture, job factors, professional development, frontline supervision, performance management, leverage external partners, and competent and engage leadership. A comparative analysis ensues, where these strategies are juxtaposed with those of frontline supervisors and frontline workers. Similarities, differences, and implications are explored.